Variasi Bahasa Masyarakat di Kecamatan Pakisjaya Kabupaten Karawang Jawa Barat - Lulu Aulia (Departement of Mathematics Education, 2023)
This research is motivated by the Karawang area which has several languages ​​used because of the many influencing factors. Differences in community groups are reflected in the variety of languages ​​of the community groups. Language in society is an inseparable unit. Therefore, language becomes an intermediary in order to interact with each other. Language variations that are formed from different usage based on the speakers. The differences that speakers use to communicate in everyday life in society. The purpose of this study was to obtain language variations in Pakisjaya sub-district, Karawang district, West Java. In this research method using description method by analyzing qualitative data. The form of the research is descriptive qualitative which in practice is in the form of a case study. The results of this study are the variations of the language obtained and examples of speakers' utterances that are carried out daily by the community. Then describe the meaning of the conversation used by the Pakisjaya sub-district community, West Java district. There are several factors influencing the occurrence of language variations. Language differences in society that become the existence of language variations.